PHILOSOPHY OF PERSONALITY IN THE CULTURE OF CREATIVITY: CREATIVITY AS A PATH TO LIFE CREATIVITY - Bohdanova, Nataliia (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
The article explores the philosophy of personality in the context of a culture of creativity, where creativity is considered a fundamental factor that contributes to the life-creativity of the individual - the process of active formation and understanding of one's own life in conditions of constant change. The relevance of this topic is due to the demands placed on a person by the constant change of the environment, which requires flexibility, the ability for innovative thinking, and deep internal development from the individual. The importance of creativity is emphasized not only as a problem-solving skill, but also as an internal process that enriches the personality, determines its ability to self-knowledge and cultural self-expression.The aim of the article is to reveal the meaning of creativity as the main means of self-creation of the individual within the framework of the culture of creativity. The proposed working hypothesis states that creativity is not only a tool for creating new ideas or objects, but also a profound way of being that gives a person the opportunity to realize themselves through the creative act. The article also examines philosophical approaches to the problem of creativity, in particular the concepts of such thinkers as I. Kant, G. Hegel, and M. Berdyaev, who consider creativity to be an important component of individual freedom and the path to her self-realization. Additionally, modern psychological and cultural studies are analyzed, which help clarify the mechanisms of creative activity and its role in personal development (A. Maslow, M. Runko and others).Particular attention is paid to the concept of "culture of creativity", which is a space that ensures the development of creative life, providing the opportunity for self-realization through the expression of aesthetic, humanistic and ethical values. Creativity in this context appears as a process that not only shapes individuality, but also creates conditions for deep interaction with others, contributing to the development of new forms of cultural expression. The author argues that creativity should be integrated into all spheres of human existence – from education to intercultural dialogue – as an important resource for the development of not only the individual, but also society as a whole, which can contribute to harmonious development and mutual understanding between people of different cultures and worldviews.The conclusions outline the prospects for further research aimed at integrating philosophical, psychological and pedagogical approaches to the formation of a creative personality in the context of modern global challenges.